(untitled) (Research, Society and Development, 2020)
In this research the allelopathic activities, of the extracts of the leaves of Ficus gomelleira Kunth (Gameleira) were addressed, as well as the phenological observations and their photochemical prospecting. The relative treatments were related to the dilutions of the extracts. The results obtained indicated that Ficus gomelleira extracts, negatively influenced the germination percentage. The germination speed index (IVG) of lettuce seeds was also negatively altered; as well as the development of lettuce stem and rootlets, which also showed a reduction in length. In relation to phenology, leaf sprouting in Ficus gomelleira occurred asynchronously for relatively short periods in the two years of observations, regardless of the pattern of rainfall. The species shows to have relevant allelopathic potentials.